Cellulosic molded body and method for producing same
The method addresses the challenge of producing thick and transparent cellulose materials by creating hydrogel and using lithium-based processes, resulting in cellulose molding with desired thickness and transparency for various applications.
Patent Information
- Application Number
- JP2023034584
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-12
- Filing Date
- 2023-03-07
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2040-10-23
AI Technical Summary
Existing technologies struggle to produce cellulose-based materials with both thickness and transparency, as methods to create thicker cellulose films often result in loss of transparency.
A manufacturing method involving the production of hydrogel through a series of processes including heating and cooling to increase cellulose compound content, followed by pressing and heating to form cellulose molding, or dissolving cellulose in a lithium aqueous solution and removing lithium bromide to achieve transparent cellulose molding.
The method produces cellulose molding with a certain thickness and transparency, suitable for applications such as packaging and structural materials, with properties like high cellulose content, low haze, and high light transmittance.
Smart Images

Figure 0007624243000002 
Figure 0007624243000003 
Figure 0007624243000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to cellulosic shaped bodies and hydrogels and methods for making the same. [Background technology]
[0002] In recent years, marine pollution caused by petroleum-derived plastics has become evident. Biodegradable plastics such as polylactic acid and microbial polyesters have been attracting attention as alternative materials to petroleum-derived plastics. However, it has been pointed out that biodegradable plastics generally decompose slowly in the ocean, and as a result, they can cause the same kind of pollution as petroleum-derived plastics (for example, accumulation in living organisms and accidental ingestion by animals).
[0003] Cellulosic compounds, which are edible polysaccharides, can be a substitute for petroleum-derived plastics. Conventionally, the use of cellulose compounds to produce membranes or molded bodies has been considered. For example, Patent Document 1 discloses a method for producing a molded body by pressurizing cellulose powder. Patent Document 2 discloses a gas-permeable membrane that utilizes the humidity sensitivity of regenerated cellulose. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 62-74609 [Patent Document 2] JP 2015-208874 A Summary of the Invention [Problem to be solved by the invention]
[0005] Meanwhile, cellophane is a film made of cellulose. Cellophane is thin, about 50 μm thick, and transparent. However, a technology for producing thicker cellophane while maintaining the transparency of cellophane has not been established so far. For example, according to the method described in Patent Document 1, a molded body having a certain thickness can be produced, but the molded body does not have transparency.
[0006] The present disclosure provides a cellulose-based molded body having a certain degree of thickness and transparency, and a method for producing the same. The present disclosure also provides a hydrogel useful for producing the cellulose-based molded body, and a method for producing the same. [Means for solving the problem]
[0007] One aspect of the present disclosure relates to a method for producing a hydrogel, which includes the following steps, in which a series of steps from step (B1) to step (C1) are repeated until the content of cellulose-based compounds in the treated material reaches 10% by mass or more. (A1) A step of preparing a material to be treated that contains a water-soluble cellulose compound and water (B1) A step of separating water from the material to be treated by heating the material to be treated. (C1) A step of cooling the treated material having an increased content of cellulose compounds after the treatment in step (B1). According to this manufacturing method, a hydrogel containing a water-soluble cellulose compound and water and having a cellulose compound content of 10 mass% or more can be obtained. This manufacturing method is based on the inventor's unique finding that the water contained in the treated material can be gradually reduced by repeating a series of steps from step (B1) to step (C1), in other words, the cellulose compound content of the treated material can be gradually increased.
[0008] One aspect of the present disclosure relates to a method for producing a cellulosic molded body from the above hydrogel, the method comprising the steps of: (a) preparing the hydrogel; (b) a step of heating the hydrogel molded body while applying a pressing force thereto (c) a step of obtaining a cellulose-based molded body having a cellulose compound content of 95% by mass or more through the heat treatment in step (b). According to this manufacturing method, it is possible to obtain a cellulose-based molded body having a certain degree of thickness (e.g., a thickness of 0.5 mm or more) and transparency (e.g., a haze of 20% or less), and having a cellulose compound content of 95% by mass or more.
[0009] One aspect of the present disclosure relates to a method for producing a cellulosic molded body using an aqueous lithium bromide solution and cellulose, the method comprising the steps of: (A2) A step of obtaining a cellulose-containing liquid by dissolving cellulose in an aqueous lithium bromide solution at a temperature of 100° C. or higher. (B2) A step of obtaining a molded body from the cellulose-containing liquid (C2) A step of removing lithium bromide from the compact by washing the compact (D2) A step of heating the compact after removing the lithium bromide while applying a pressing force to it (E2) A step of obtaining a cellulose-based molded body having a cellulose content of 95% by mass or more through the heat treatment in step (D2). According to this method, by heating the molded body after removing the lithium bromide while applying a pressing force, it is possible to obtain a cellulose-based molded body having a certain degree of thickness (e.g., a thickness of 0.5 mm or more) and transparency (e.g., a haze of 50% or less), and having a cellulose compound content of 95% by mass or more. Effect of the Invention
[0010] According to the present disclosure, there is provided a cellulose-based molded body having a certain degree of thickness and transparency, and a method for producing the same. Also, according to the present disclosure, there is provided a hydrogel useful for producing the cellulose-based molded body, and a method for producing the same. [Brief description of the drawings]
[0011] [Figure 1]FIG. 1 is a perspective view that illustrates a schematic example of a cellulose-based structure formed from a cellulose-based molded body according to an embodiment of the present disclosure. [Diagram 2] FIG. 2 is a graph showing an example of the process in which the content of methylcellulose (a cellulose compound) in the treated material gradually increases. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, a detailed description will be given of several embodiments of the present disclosure. The present invention is not limited to the embodiments described below. In the numerical ranges described in stages in this specification, the upper limit or lower limit of a certain numerical range may be replaced by the upper limit or lower limit of another numerical range. In the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced by a value shown in the examples. In this specification, hydrogel means a solid dispersion composition containing water.
[0013] [First embodiment] (Hydrogel and its manufacturing method) The method for producing a hydrogel according to this embodiment includes the following steps, in which a series of steps from step (B1) to step (C1) are repeated until the content of cellulose-based compounds in the treated material reaches 10 mass % or more. (A1) A step of preparing a material to be treated that contains a water-soluble cellulose compound and water (B1) A step of separating water from the material to be treated by heating the material to be treated. (C1) A step of cooling the treated material having an increased content of cellulose compounds after the treatment in step (B1). Each step and the hydrogel produced will be described below.
[0014] <Process (A1)> Step (A1) is a step of preparing a material to be treated that contains a water-soluble cellulose compound and water. The water-soluble cellulose compound is a compound that dissolves at 0.5 parts by mass or more in 100 parts by mass of water at 25°C and has some or all of the hydrogen atoms of the hydroxyl groups contained in cellulose substituted with substituents other than hydrogen atoms. Examples of such cellulose compounds include methylcellulose and hydroxypropyl methylcellulose (HPMC). As methylcellulose and hydroxypropyl methylcellulose, known products can be used as appropriate. Examples of commercially available methylcellulose include "Metolose MCE-4000 for food additives" manufactured by Shin-Etsu Chemical Co., Ltd. Examples of commercially available hydroxypropyl methylcellulose include "Metolose SFE-4000 for food additives" manufactured by Shin-Etsu Chemical Co., Ltd.
[0015] The degree of substitution in the water-soluble cellulose compound is preferably 45% or more, more preferably 60% or more, from the viewpoint of promoting phase separation when the material to be treated is heated, and is preferably 65% or less, more preferably 63% or less, from the viewpoint of increasing solubility in water. In this specification, the degree of substitution in the water-soluble cellulose compound means the ratio of the introduced substituents to the total amount of hydroxyl groups and the introduced substituents contained in the cellulose compound.
[0016] The weight average molecular weight of the water-soluble cellulose compound is not particularly limited, but is, for example, from 100000 to 200000. In the present specification, the weight average molecular weight refers to the weight average molecular weight determined by GPC method in terms of standard polystyrene.
[0017] The content of the water-soluble cellulose compound in the material to be treated prepared in this step is not particularly limited, but is, for example, 0.5 to 4.0 mass% based on the total amount of the material to be treated. The material to be treated may contain components other than the water-soluble cellulose compound and water. Examples of such components include carbon nanofibers. The content of such components is not particularly limited, but is, for example, 0.01 to 15 mass% based on the total amount of the material to be treated.
[0018] The method for preparing the treated material is not particularly limited, but for example, the treated material can be obtained by mixing a water-soluble cellulose compound, water, and, if necessary, components other than the water-soluble cellulose compound and water. The mixing means is not particularly limited, but for example, a magnetic stirrer can be used.
[0019] <Process (B1)> Step (B1) is a step of separating water from the material to be treated by heating the material to be treated. By heating the material to be treated, the material to be treated undergoes phase separation into a gel containing a cellulose compound and water. The heating temperature of the material to be treated is not particularly limited as long as it is a temperature at which phase separation into a gel containing a cellulose compound and water is possible, but is, for example, 60 to 150°C, and may be 80 to 120°C. The heating time of the material to be treated is not particularly limited, but is, for example, 0.5 to 24 hours.
[0020] In step (B1), the object to be treated may be heated while it is contained in a container. This allows the object to be phase-separated into a gel containing a cellulose compound and water, and then the water can be separated from the object to be treated by discharging the water from the container. When the object to be treated is heated while it is contained in a container, it is preferable that the container is sealed in order to prevent the surface of the gel containing a cellulose compound from drying. The means for heating the object to be treated is not particularly limited, and may be, for example, an oven.
[0021] <Process (C1)> Step (C1) is a step of cooling the material to be treated that has been treated in step (B1) and has an increased content of cellulose compounds. The cooling temperature of the material to be treated is not particularly limited as long as the material to be treated is a temperature at which the material to be treated becomes an aqueous solution or a sol, and is, for example, −10 to 25° C. The cooling time of the material to be treated is not particularly limited, and is, for example, 0.5 to 24 hours. The cooling means for the material to be treated is not particularly limited, and for example, a refrigerator can be used. The material to be treated may be cooled while it is contained in a container.
[0022] By repeating a series of steps from step (B1) to step (C1), the content of cellulose compounds in the treated material can be gradually increased (see FIG. 2). The number of times of the series of steps from step (B1) to step (C1) is not particularly limited, but from the viewpoint of increasing the content of cellulose compounds in the treated material, it is, for example, 2 to 15 times or 2 to 5 times, and preferably 4 times or more.
[0023] <Hydrogel> According to the above-mentioned production method, a hydrogel is produced which contains a water-soluble cellulose compound and water and has a cellulose compound content of 10% by mass or more. From the viewpoint of lowering the gel-to-sol phase transition temperature, the cellulose compound content in this hydrogel is preferably 10% by mass or more, more preferably 12.5% by mass or more, and even more preferably 15% by mass or more. The compressive elastic modulus of the hydrogel at 25°C is preferably 5 kPa or more, more preferably 10 kPa or more, and even more preferably 30 kPa or more. The compressive elastic modulus refers to a value measured as the slope of the elastic region in a compression test using a mechanical testing machine at 25°C.
[0024] The hydrogel of the present embodiment preferably has a self-repairing property. In the present specification, the term "self-repairing" means that, even when the hydrogel is cut and the cut surfaces are adhered, the values of the compressive elastic modulus and the breaking strain of the hydrogel are 95% or more based on the values of the compressive elastic modulus and the breaking strain of the hydrogel when the hydrogel is not cut. The method of adhering the hydrogel is not particularly limited, and examples thereof include the following methods. That is, distilled water or ion-exchanged water is applied to the cut surfaces of the hydrogel. Then, the hydrogel is fixed in a state where the cut surfaces are adhered together. The fixed hydrogel is cooled, and the hydrogel is heated after cooling. In the present specification, the breaking strain of the hydrogel means a value measured as a strain value at the time of breaking of a test piece in a compression test using a mechanical testing machine at 25°C.
[0025] The gel-to-sol phase transition temperature of the hydrogel of this embodiment is preferably 20° C. or lower, more preferably 10° C. or lower, and even more preferably 5° C. or lower. In this specification, the gel-to-sol phase transition temperature of the hydrogel can be determined by adjusting the temperature of an object to a predetermined temperature and determining whether or not the object can be grasped with the hand.
[0026] (Cellulosic Molded Body and Its Manufacturing Method) The method for producing a cellulose-based molded article according to this embodiment includes the following steps. (a) A step of preparing a hydrogel according to the present embodiment (b) A step of heating the hydrogel molded body while applying a pressing force. (c) a step of obtaining a cellulose-based molded body having a cellulose compound content of 95% by mass or more through the heat treatment in step (b). Each step and the cellulosic molded article produced will be described below.
[0027] <Process (a)> Step (a) is a step of preparing the hydrogel according to this embodiment. The hydrogel and the method for producing the same are as described above.
[0028] <Process (b)> Step (b) is a step of heating the hydrogel molded body while applying a pressing force to the hydrogel molded body. The hydrogel molded body can be obtained, for example, by cooling the hydrogel in a state where the hydrogel is placed in a container or a mold, causing a phase transition to a sol having fluidity, and then heating the hydrogel to cause a phase transition to a gel.
[0029] The pressing force applied to the hydrogel molded body may be appropriately set depending on the heating temperature and heating time described later. The pressing force applied to the hydrogel molded body is, for example, 10 g / cm from the viewpoint of maintaining the smoothness of the hydrogel surface to be dried by heating and obtaining a dense cellulose-based molded body. 2 Above 20-1000g / cm 2 Or 30~100g / cm 2 The heating temperature of the hydrogel molded body may be appropriately set so that the content of the cellulose compound after the heat treatment is 95% by mass or more, for example, 60 to 150° C. The heating time of the hydrogel molded body may be appropriately set so that the content of the cellulose compound after the heat treatment is 95% by mass or more, for example, 0.5 to 48 hours. The heating means for the hydrogel molded body is not particularly limited, and may be, for example, an oven.
[0030] <Process (c)> Step (c) is a step of obtaining a cellulose-based molded body having a cellulose-based compound content of 95% by mass or more through the heat treatment in step (b). The cellulose-based compound content in the cellulose-based molded body is, for example, 95% by mass or more or 100% by mass. The water content in the cellulose-based molded body is, for example, 5% by mass or less, and may be 1% by mass or less or 0% by mass.
[0031] <Cellulosic molded body> According to the above-mentioned manufacturing method, a cellulose-based molded body having a thickness of 0.5 mm or more, a haze of 20% or less, and a cellulose compound content of 95% by mass or more is manufactured. Examples of applications of the cellulose-based molded body include packaging materials, packing materials, and construction materials. Examples of the form of the cellulose-based molded body include plates and articles having a predetermined shape. The thickness of the cellulose-based molded body may be appropriately set according to the application or form of the cellulose-based molded body, and may be, for example, 0.5 mm or more, 1 to 5 mm, or 1 to 10 mm.
[0032] The haze of the cellulose-based molded body is preferably 18% or less, and more preferably 15% or less. In this specification, the haze of the cellulose-based molded body means a value measured by a haze meter for a cellulose-based molded body having a thickness of 0.5 mm or more.
[0033] The total light transmittance of the cellulose-based molded body is preferably 60% or more, and more preferably 75% or more. In this specification, the total light transmittance of the cellulose-based molded body means a value calculated by measuring the amount of incident light and the amount of total transmitted light, and calculating the total light transmittance = (total transmitted light amount) / (incident light amount) x 100. The incident light amount and the total transmitted light amount are values measured by a haze meter.
[0034] The flexural modulus of the cellulose-based molded article is preferably 1 GPa or more, and more preferably 5 GPa or more. In this specification, the flexural modulus refers to a value measured by a three-point bending test using a mechanical testing machine.
[0035] (Cellulosic structure and method for producing same) The cellulose-based structure of this embodiment is obtained by preparing two or more of the above-mentioned cellulose-based molded bodies, adhering them together, and then completely drying them. More specifically, the cellulose-based structure of this embodiment is manufactured, for example, through the following steps. First, distilled water or ion-exchanged water is applied to the parts of the cellulose-based molded bodies to be bonded together. The cellulose-based molded bodies are bonded together via the water. The bonded cellulose-based molded bodies are cooled to promote adhesion. The cooled cellulose-based molded bodies are heated to completely dry them.
[0036] The shape of the cellulose-based structure of this embodiment is, for example, a container or a laminate. Fig. 1 is a perspective view showing an example of a cellulose-based structure. The cellulose-based structure 10 shown in Fig. 1 is a container, and is composed of five cellulose-based molded bodies 1, 2, 3, 4, and 5. The cellulose-based molded bodies 1, 2, 3, and 4 form the side surfaces of the container, and the cellulose-based molded body 5 forms the bottom surface.
[0037] [Second embodiment] (Cellulosic Molded Body and Its Manufacturing Method) In the above-described first embodiment, a hydrogel is prepared using a water-soluble cellulose compound, and then a cellulose-based molded body is manufactured from the hydrogel. However, a water-insoluble cellulose may be used as a raw material. That is, the manufacturing method of the cellulose-based molded body according to this embodiment includes the following steps. (A2) A step of obtaining a cellulose-containing liquid by dissolving cellulose in an aqueous lithium bromide solution at a temperature of 100° C. or higher. (B2) A step of obtaining a molded body from the cellulose-containing liquid (C2) A step of removing lithium bromide from the compact by washing the compact (D2) A step of heating the compact after removing the lithium bromide while applying a pressing force to it (E2) A step of obtaining a cellulose-based molded body having a cellulose content of 95% by mass or more through the heat treatment in step (D2). Each step and the cellulosic molded article produced will be described below.
[0038] <Process (A2)> Step (A2) is a step of obtaining a cellulose-containing liquid by dissolving cellulose in an aqueous lithium bromide solution under a temperature condition of 100°C or higher. Any known cellulose can be used as appropriate. An example of a commercially available cellulose product is "BEMCOT" manufactured by Asahi Kasei Corporation. The weight-average molecular weight of the cellulose is not particularly limited, but is, for example, 5000 to 1500000. The concentration of lithium bromide in the aqueous lithium bromide solution is, for example, 55 to 60% by mass, and may be 50 to 65% by mass, based on the total amount of the aqueous lithium bromide solution.
[0039] The temperature when dissolving cellulose in the lithium bromide aqueous solution is, for example, 100 to 160° C., and may be 90 to 180° C. The amount of cellulose when dissolving cellulose in the lithium bromide aqueous solution is, for example, 0.5 to 10 parts by mass, and may be 0.1 to 25 parts by mass, relative to 100 parts by mass of the lithium bromide aqueous solution.
[0040] The cellulose-containing liquid may contain components other than cellulose, lithium bromide, and water. Examples of such components include carbon nanofibers. The content of such components is, for example, 0.01 to 25 mass% based on the total amount of the cellulose-containing liquid.
[0041] <Process (B2)> Step (B2) is a step of obtaining a molded body from the cellulose-containing liquid. The method of obtaining the molded body is not particularly limited, but for example, the cellulose-containing liquid heated in step (A2) is cooled in a container as it is. The shape of such a container is not particularly limited, and can be appropriately changed according to the shape of the desired cellulose-based molded body. The temperature at which the cellulose-containing liquid is cooled is not particularly limited as long as it is a temperature at which the cellulose-containing liquid undergoes a phase change from sol to gel.
[0042] <Process (C2)> Step (C2) is a step of removing lithium bromide from the compact by washing the compact. The washing liquid used for washing the compact is not particularly limited as long as it can remove lithium bromide from the compact, and examples thereof include distilled water and ion-exchanged water. The method for washing the compact is not particularly limited, and examples thereof include a method of immersing the compact in the above-mentioned washing liquid. Whether the compact has been sufficiently washed or not can be determined based on, for example, the concentration of lithium bromide dissolved in the water used for washing.
[0043] <Process (D2)> Step (D2) is a step of heating the compact after removing lithium bromide while applying a pressing force to the compact. The treatment conditions and heating means of step (D2) can be the same as those of step (b) in the first embodiment.
[0044] <Process (E2)> Step (E2) is a step of obtaining a cellulose-based molded body having a cellulose content of 95% by mass or more through the heat treatment in step (D2). The cellulose content in the cellulose-based molded body may be 95% by mass or more or 100% by mass. The water content in the cellulose-based molded body may be, for example, 5% by mass or less, 1% by mass or less, or 0% by mass.
[0045] <Cellulosic molded body> According to the above-mentioned manufacturing method, a cellulose-based molded body having a thickness of 0.5 mm or more, a haze of 50% or less, and a cellulose content of 95% by mass or more is manufactured. The haze of the cellulose-based molded body according to this embodiment is preferably 40% or less, more preferably 30% or less. Other physical properties and uses of the cellulose-based molded body according to this embodiment can be the same as those of the cellulose-based molded body according to the first embodiment.
[0046] (Cellulosic structure and method for producing same) The cellulose-based structure of this embodiment is obtained by preparing two or more of the above-mentioned cellulose-based molded bodies and bonding them together. The means for bonding the cellulose-based molded bodies is not particularly limited, but examples thereof include wood glue and instant adhesive. The shape of the cellulose-based structure of this embodiment may be the same as that of the cellulose-based structure of the first embodiment. EXAMPLES
[0047] The present disclosure will now be described in more detail with reference to examples, but the present invention is not limited to the following examples.
[0048] The hydrogel and cellulosic molded article according to the first embodiment were produced as follows. [Hydrogel production] Example 1a (Process (A1)) Powdered methylcellulose (product name: "Metolose MCE-4000 for food additives" manufactured by Shin-Etsu Chemical Co., Ltd.) was dissolved in distilled water as a water-soluble cellulose compound to prepare a material to be treated in which 2% by mass of methylcellulose was dissolved. Next, 1000 g of the obtained material to be treated was poured into a heat-resistant container (length 12 cm × width 12 cm × height 10 cm).
[0049] (Process (B1)) The heat-resistant container containing the material to be treated was heated in an oven at 110°C for 3 hours, causing the material to be separated into a methylcellulose gel and separated water. The separated water was then discharged from the heat-resistant container.
[0050] (Process (C1)) The methylcellulose gel was allowed to cool at room temperature, and then cooled in a refrigerator with an internal temperature of 4° C. for 1 hour to obtain a treated material containing methylcellulose and water.
[0051] After step (A1), the treated material was subjected to steps (B1) and (C1) seven times to obtain a hydrogel (length 8 cm × width 8 cm × thickness 1 cm) containing methylcellulose. Figure 2 is a graph showing the gradual increase in the methylcellulose content of the treated material. The obtained hydrogel had no cracks or fissures and was not fluid, so it was self-supporting and stable even at room temperature (25°C). The obtained hydrogel was capable of being held by hand. The composition of the obtained hydrogel is shown in Table 1.
[0052] Example 1b A hydrogel was obtained in the same manner as in Example 1a, except that the treatment of step (B1) and step (C1) was performed on the treated object four times instead of seven times. The obtained hydrogel had no cracks or fissures and no fluidity, and was self-supporting and stable even at room temperature (25°C). The obtained hydrogel was capable of being held by hand. The composition of the obtained hydrogel is shown in Table 1.
[0053] Example 1c A hydrogel was obtained in the same manner as in Example 1a, except that hydroxypropyl methylcellulose (manufactured by Shin-Etsu Chemical Co., Ltd., product name: "Metolose SFE-4000 for food additives") was used instead of methylcellulose as the water-soluble cellulose compound. The obtained hydrogel had no cracks or fissures and no fluidity, and was therefore self-supporting and stable even at room temperature (25°C). The obtained hydrogel was capable of being held by hand. The composition of the obtained hydrogel is shown in Table 1.
[0054] <Comparative Example 1a> The treatment was carried out in the same manner as in Example 1a, except that the treatments in steps (B1) and (C1) were carried out once instead of seven times. The resulting treated material was a methylcellulose sol at room temperature (25°C) and did not become a hydrogel. The composition of the resulting treated material is shown in Table 1.
[0055] [Table 1]
[0056] [Measurement of compressive elastic modulus of hydrogel] The hydrogel according to the embodiment was hollowed out to obtain a cylindrical test piece (diameter 25 mm × thickness 10 mm). The obtained sample was measured for compressive modulus at 25°C. The compressive modulus was measured by performing a compression test on the cylindrical test piece using a mechanical testing machine (manufactured by Shimadzu Corporation, product name: "EZ-TEST") The compressive modulus of the hydrogel according to Example 1a was 50 kPa.
[0057] [Measurement of storage modulus of hydrogel] The storage modulus of the hydrogel of the example was measured at 20°C, 40°C and 60°C. A rheometer (Anton Paar MCR501) was used for the measurement. The measurement conditions were a heating rate of 1°C / min, a shear strain of 0.001%, and a frequency scan mode (0.1 to 100 rad / sec). The storage modulus of the hydrogel of Example 1a at 20°C, 40°C and 60°C was 30 kPa, 40 kPa and 60 kPa, respectively.
[0058] [Evaluation of self-healing properties of hydrogels] The hydrogel according to the embodiment was hollowed out to obtain two cylindrical samples (diameter 25 mm x thickness 10 mm). One of the samples was cut with a knife to form two semi-cylinders. Distilled water was then applied to the cut surface using a cotton swab. The cut surfaces were then attached to each other, and vinyl tape was wrapped around the outer periphery to fix the two semi-cylinders in a bonded state. The two fixed semi-cylinders were stored in a refrigerator with an internal temperature of 4°C for one hour, then heated in an oven at 110°C for 15 minutes, and allowed to cool at room temperature after heating. After cooling, the cut surfaces of the two semi-cylinders were adhered to each other and had the same shape as the other sample that was not cut. In addition, the compressive modulus was measured for the cut and adhered sample and the uncut sample in the same manner as the measurement of the compressive modulus of the hydrogel. In addition, the breaking strain at 25°C was measured for both samples. The compressive modulus was measured by performing a compression test on cylindrical test pieces using a mechanical testing machine (manufactured by Shimadzu Corporation, product name: "EZ-TEST") The compressive modulus and breaking strain of the cut and adhered sample were determined to have self-repairing properties if the compressive modulus and breaking strain of the uncut sample were 95% or more.
[0059] The compressive elastic modulus of the hydrogel in Example 1a was 50 kPa and the breaking strain was 40% for both the cut and adhered sample and the uncut sample. In other words, the hydrogel in Example 1a had self-repairing properties.
[0060] [Measurement of phase transition temperature of hydrogel] The phase transition temperatures of the hydrogels according to the examples were determined by adjusting the temperature of the hydrogels according to the examples to a predetermined temperature and determining whether or not an object could be grasped with the hand. The phase transition temperatures of the hydrogels according to the examples 1a and 1b were 10°C and 20°C, respectively.
[0061] [Production of cellulosic molded bodies] The hydrogel according to the example was subjected to the following steps (b) and (c) to obtain a cellulose-based molded article.
[0062] (Step (b) and step (c)) The hydrogel according to each example was placed in a container. A weight was placed on the upper surface of the hydrogel via a plate, so that the weight of the hydrogel was 30 g / cm 2 In this state, the hydrogel was dried in an oven heated to 110°C until completely dry. As a result, a cellulose-based molded body (thickness 2 mm) was obtained. The obtained cellulose-based molded body was dense without any cracks or fissures and had a density of 1.3 g / cm. 3 The methylcellulose content in the cellulose-based molded bodies according to Examples 1a and 1b was both 100% by mass.
[0063] [Measurement of haze of cellulose-based molded body] The haze in the thickness direction of the cellulose-based molded body according to each example was measured. For the measurement, a haze meter HZ-V3 (device name, manufactured by Suga Test Instruments Co., Ltd.) was used. The measurement was performed using a double beam method (light source: C light). The haze of the cellulose-based molded body according to Examples 1a and 1b was both 15%.
[0064] [Total light transmittance of cellulose-based molded body] The total light transmittance in the thickness direction of the cellulose-based molded body according to each Example was measured. The total light transmittance was calculated by measuring the amount of incident light and the amount of total transmitted light, and the total light transmittance was calculated as total light transmittance = (total transmitted light amount) / (incident light amount) x 100. A haze meter HZ-V3 (device name, manufactured by Suga Test Instruments Co., Ltd.) was used for the measurement. The total light transmittance of the cellulose-based molded body according to Examples 1a and 1b was both 80%.
[0065] [Measurement of bending modulus of cellulose-based molded body] The cellulose-based molded bodies according to each Example were subjected to a three-point bending test using a mechanical testing machine (manufactured by Shimadzu Corporation, product name: "EZ-TEST") to measure the flexural modulus. The measurement conditions were a support distance of 40 mm and a test speed of 1 mm / min. The flexural modulus of the cellulose-based molded bodies according to Examples 1a and 1b was both 2.5 GPa.
[0066] [Production of cellulose-based structures] Five cellulose-based molded bodies according to each example were prepared, and distilled water was applied to the main surfaces of these cellulose-based molded bodies using a cotton swab. Next, the five cellulose-based molded bodies were laminated together so that the main surfaces of each cellulose-based molded body faced each other through the water. Next, the five laminated cellulose-based molded bodies were stored in a refrigerator with an internal temperature of 4°C for one hour to promote adhesion between the cellulose-based molded bodies. Thereafter, the five cellulose-based molded bodies were heated in an oven at 110°C for 10 minutes to make the laminated surfaces of the cellulose-based molded bodies opaque. Next, the five cellulose-based molded bodies were clamped with a clip (a double clip for stationery) so that a force was applied in a direction perpendicular to the main surfaces of the cellulose-based molded bodies, and heated in an oven at 110°C for two hours, and the five cellulose-based molded bodies were completely dried to obtain a cellulose-based structure in which the five cellulose-based molded bodies were adhered to each other. The cellulosic structure was 1 cm thick, dense without splits or cracks, and could be sawed, drilled, and nailed.
[0067] The cellulose-based molded body and the cellulose-based structure according to the second embodiment were produced as follows.
[0068] [Production of cellulosic molded bodies] Example 2a A cellulose-based molded article was obtained by carrying out the following steps (A2) to (E2).
[0069] (Process (A2)) Lithium bromide was dissolved in distilled water to prepare an aqueous solution of lithium bromide with 60% by mass of lithium bromide dissolved therein. Cellulose (manufactured by Asahi Kasei Corporation, product name: "BEMCOT") was dissolved in the prepared aqueous solution of lithium bromide so that the concentration of cellulose was 2% by mass, and the solution was stirred while being heated to 120°C or higher to prepare a cellulose-containing liquid.
[0070] (Process (B2)) 700 g of the obtained cellulose-containing liquid was poured into a heat-resistant container (12 cm length × 12 cm width × 10 cm height) and allowed to cool at 25°C to obtain a gel-like molded product.
[0071] (Process (C2)) The resulting molded body was washed by immersing it in distilled water to remove the encapsulated lithium bromide.
[0072] (Process (D2) and Process (E2)) The compact from which the lithium bromide had been removed was placed in a container. Next, a weight was placed on the upper surface of the compact via a plate, so that the weight was 30 g / cm 2 A pressing force of 100 mm was applied. In this state, the molded body was dried in an oven heated to 110° C. until completely dry. As a result, a cellulose-based molded body (thickness: 2 mm) was obtained. The cellulose content of the obtained cellulose-based molded body was 100% by mass. The obtained cellulose-based molded body was dense without any cracks or fissures, and had a density of 1.3 g / cm 3 It was.
[0073] [Measurement of haze, total light transmittance and bending modulus of cellulose-based molded body] The haze, total light transmittance, and bending modulus of the obtained cellulose-based molded article were measured in the same manner as in Example 1a, and the results were that the haze was 50%, the total light transmittance was 75%, and the bending modulus was 5.0 GPa.
[0074] [Production of cellulose-based structures] Five cellulose-based molded bodies were prepared and used to assemble a box-shaped container with four sides and one bottom (see Figure 1). Specifically, wood glue was applied with a cotton swab to the places where the cellulose-based molded bodies came into contact with each other. Next, the five cellulose-based molded bodies were temporarily secured together with tape and left to stand until the wood glue hardened, yielding a container. The resulting container was solid, without any cracks or breaks, and could be cut with a saw, drilled with a drill, and nailed into. [Industrial Applicability]
[0075] According to the present disclosure, there is provided a cellulose-based molded body having a certain degree of thickness and transparency, and a method for producing the same. Also, according to the present disclosure, there is provided a hydrogel useful for producing the cellulose-based molded body, and a method for producing the same. [Explanation of symbols]
[0076] 1 to 5: Cellulosic molded body, 10: Cellulosic structure
Claims
1. (A2) a step of obtaining a cellulose-containing liquid by dissolving cellulose in an aqueous lithium bromide solution at a temperature of 100° C. or higher; (B2) obtaining a molded body from the cellulose-containing liquid; (C2) removing lithium bromide from the compact by washing the compact; (D2) a step of heating the compact after removing the lithium bromide while applying a pressing force to the compact; (E2) a step of obtaining a cellulose-based molded body having a cellulose content of 95% by mass or more through the heat treatment in step (D2); A method for producing a cellulosic molded body, comprising:
2. The method for producing a cellulose-based molded article according to claim 1, wherein the cellulose has a weight average molecular weight of 5,000 to 1,500,000.
3. The method for producing a cellulose-based molded body according to claim 1 or 2, wherein the lithium bromide concentration of the lithium bromide aqueous solution is 50 to 65 mass% based on the total amount of the lithium bromide aqueous solution.
4. The method for producing a cellulose-based molded body according to any one of claims 1 to 3, wherein the temperature when dissolving the cellulose in the lithium bromide aqueous solution is 180°C or lower.
5. A method for producing a cellulose-based molded body described in any one of claims 1 to 4, wherein the cellulose-based molded body has a thickness of 0.5 mm or more and a haze of 50% or less.
Citation Information
Patent Citations
High-strength transparent cellulose material and preparation method thereof
CN101880410A
Adapalene gel and method for preparing same
CN103417473A
Manufacture of cellulose molded body
JP1987074609A
Production of methylcellulose binder to be contained in ceramic molding
JP1991041101A
Solvent for dissolution of polysaccharide material
JP2001316401A